Determinants of guest experience and its influence on resort guest loyalty / Nor Diyana Mohammed Shobri - Mohammed Shobri, Nor Diyana (2020)
The premise of this study is that in a consumer purchase decision process, there must be some phenomena that trigger the consumer‟s mind about their future consumption experience. In other words, consumers tend to develop perception and expectation towards their consumption experience. However, the consumer‟s perception and expectation will only develop if they are activated by certain events. Customer-based brand equity and eWOM communication are constructs that explain possible key factors towards the development of consumer‟s perception and expectation, and subsequently their consumption experience. By applying Experience Economy concept, supported by functional experience and emotional experience concepts as well as recommendations from the literatures, this study sets out to investigate the determinants of guest experience in the Malaysian resort settings. A survey approach using questionnaire was applied to collect responses from 500 tourists staying for at least one night at the beach and island resorts in Malaysia. A structural equation modeling (Partial Least Square or PLS-SEM) approach was subsequently applied to examine the direct effects of guest experience. Findings from this study revealed that the hypothesized relationships between brand awareness and guest experience (service environment, service employee, esthetic experience and escapism experience) were not supported. However, brand association and perceived service quality were found interrelated with guest experience (service environment, service employee, esthetic experience and escapism experience). In relation to the eWOM, the findings indicated that the hypothesized relationship between eWOM and four dimensions of guest experience (service environment, service employee and esthetic experience escapism experience) was supported. Findings also confirmed that guest experience is related with guest loyalty. This study makes several theoretical contributions. Towards the end managerial contributions and several potential opportunities for future research are delineated.